If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 9 = 7 Reorder the terms: 9 + 2a = 7 Solving 9 + 2a = 7 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 2a = 7 + -9 Combine like terms: 9 + -9 = 0 0 + 2a = 7 + -9 2a = 7 + -9 Combine like terms: 7 + -9 = -2 2a = -2 Divide each side by '2'. a = -1 Simplifying a = -1
| -6x-18=6 | | 9n+10=-17 | | 15+2n=8+3n | | 12=-x+1 | | -7x-15=34 | | (.25)16+30=x | | x^2-9=9 | | 5*5-6=x | | K+3K+32=27+2+5K | | 3y+3=-36 | | .50(3*2+68)=x | | 6(3*64-8*4)=x | | 12-3y=52+5 | | 5a=35 | | 29-x=13 | | r=-3 | | 17x-12=114+3x | | 5-7x=-15-3x | | -0.25y=16 | | x-2y+5=8 | | 8x^3+10x^2-5x-3=0 | | X+(-6)=9 | | -10p+9=12 | | 14c+35= | | 68-4*(3-1)3=c | | 6b+8= | | x^2+4bx+2b=0 | | X^3+2x^2-8x= | | 2x^12+3x= | | -3=5-t | | 173x+12=185 | | 173x+12=194 |